Polymer surface characterization - Sabbatini, Luigia (De Gruyter graduate., 2014)
This book provides a comprehensive approach to the surface analysis of polymers of technological interest by means of modern analytical techniques. Case studies are critically discussed by experts in the field. This book is aimed at graduate students but also at newcomers to the field of surface characterization and chemical analysis but also generally interested in polymeric materials.